The Authorship of Ezra and Nehemiah in Light of Differences in Their Ideological Background - Amzalag, Nisim (Journal of Biblical literature, 2018)
The books of Ezra and Nehemiah differ in their definition of the repatriates from Babylon, the boundaries of the in-group, the appellations of God, the celebration of the Sukkot festival, the status of the priests, the prestige bestowed on Ezra, and the attitude toward the foreign Yahwistic singers (Ezrahites) who took part in musical worship at the Jerusalem temple. The intersection of all these differences reveals the contrasting ideological backgrounds of these two books. In Ezra, the returnees from Babylon and their religious elite (priests, Levites, and prophets) constitute the nucleus preserved by YHWH from destruction from which Israel as a whole is expected to regenerate. Both this view of the repatriates as the sole legitimate remnant and its ideological consequences are challenged in Nehemiah. These differences are perceptible not only when the first-person narrative sections in Ezra and Nehemiah are compared (the so-called Ezra and Nehemiah memoirs) but also in the third-person narration segments. These positions are consistent throughout Ezra and Nehemiah, leading to the conclusion that the two books were composed and/or edited by two distinct authors who expressed contrasting views on the theological importance of the Babylonian exile.